Shear strength evaluation of bentonite stabilised with recycled materials - Hasan, U.; Chegenizadeh, Amin; Budihardjo, M.; Nikraz, Hamid (Taiwan Geotechnical Society, 2016)
The volumetric deviations in montmorillonite-rich clays like bentonite render such soils unsuitable to support overlying pavement and foundation structures. Moreover, green construction and sustainable waste management practices have adapted use of waste recycled materials for engineering purposes. This study explores the feasibility of using recycled construction and demolition waste and ground granulated blast furnace slag for developing shear strength properties of bentonite clay. Direct shear tests were performed on specimens from bentonite and bentonite-stabiliser composites to evaluate the effect of both stabilisers under different curing times and percentages. Microanalyses were conducted to obtain microstructural, mineralogical and elemental composition of the stabilised and unstabilised samples. Results exhibit that shear strength increased with increasing stabiliser percentages and curing time, and the effects were more enhanced on higher stabiliser dosages and curing periods. Sample cohesion value increased from 58.90 kPa for pure bentonite sample to 67.26 kPa for the maximum additive percentages of 5% slag and 20%construction waste (sample S3G5), after 28 days of curing. The internal friction angle also increased by 7.3° from the pure sample to the S3G5 bentonite-stabilisers composite specimen. Peak shear stress values also showed a development of 55.95 kPa after additive induction and 28 days curing, for 200 kPa of normal stress. Curing period also affected the development of cohesion and peak shear strength of the stabilised samples. Internal frictional angle for sample S3G5 also escalated by 2.3°, after 28 days, from the 25.0° value after sample curing of 1 day. Scanning Electron Microscopy (SEM) micrographs and Energy Dispersive Spectroscopy (EDS) spectra show that stabilisers occupied vesicles and cracks found in construction waste particles, resulting in better particle interlocking mechanism and greater shear strength.